(untitled) (Journal of Political Science, 2025)
This article examines the connection between development and geopolitics in Nepal. The primary assertion made here is that development cannot be viewed solely through its principles, as commonly perceived, but is also significantly shaped by geopolitical motivations. It investigates the interactions among geopolitics, non-state entities, and foreign aid, offering a systematic qualitative evaluation. It also explores the relationship between development and geopolitics, indicating that development frequently hinges more on geopolitical factors than on the process of development itself. This might clarify why, despite continuous external assistance and internal initiatives, development has not advanced to a stage that can offer economic opportunities for all individuals. Support and initiatives for development from the outside often reflect an external perspective on Nepal’s progress. Furthermore, development in Nepal has become highly (geo)politicized and the country struggles to determine which projects to undertake and which to avoid this trend will continue in the coming days as well. It contends that Nepal must take a proactive approach to tackling existing geopolitical issues while furthering its development goals.